2018
DOI: 10.21273/hortsci13370-18
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Endophytes in Knock Out® Rose and Performance Effects of Entomopathogens on Marigold and Zinnia

Abstract: Endophytic fungi are increasingly studied for their ability to enhance plant performance in field crops, yet there are few equivalent studies in floricultural crops. Given the economic importance of these crops and pressures faced by growers to produce plants of high aesthetic quality, we surveyed the natural occurrence of foliar fungal endophytes in Knock Out Ò roses to identify candidate beneficial isolates. We also tested the effects of entomopathogenic fungal inocula on marigold and zinnia plant growth usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…LCOs from fungi also operate as plant growth regulators by indirectly impacting plant biomass production, shoot and root growth, lateral root branching and seed germination (Oldroyd et al 74; Khan et al 49; Maillet et al 65; Tanaka et al 0104). Root colonization by EIPF results in extensive root development in the host plant, suggesting EIPF may release a similar symbiosis factor prior to root colonization (Jaber and Enkerli 44; Heinz et al 38; Razinger et al 89). For example, M. robertsii , M. acridum , M. anisopliae , M. brunneum and B. bassiana produce indole‐3‐acetic acid (IAA), which promotes plant growth (Liao et al 60).…”
Section: Signalling Factorsmentioning
confidence: 99%
“…LCOs from fungi also operate as plant growth regulators by indirectly impacting plant biomass production, shoot and root growth, lateral root branching and seed germination (Oldroyd et al 74; Khan et al 49; Maillet et al 65; Tanaka et al 0104). Root colonization by EIPF results in extensive root development in the host plant, suggesting EIPF may release a similar symbiosis factor prior to root colonization (Jaber and Enkerli 44; Heinz et al 38; Razinger et al 89). For example, M. robertsii , M. acridum , M. anisopliae , M. brunneum and B. bassiana produce indole‐3‐acetic acid (IAA), which promotes plant growth (Liao et al 60).…”
Section: Signalling Factorsmentioning
confidence: 99%
“…Rosa is an agriculturally important genus. Several studies have documented Rosa ‐associated fungi, including endophytes (Salgado‐Salazar & Cepero de García, 2005; Kaul et al, 2008; Wani et al, 2010; Li et al, 2012; Menkis et al, 2014; Dasari et al, 2015; Heinz et al, 2018; Suwannarach et al, 2018; Zhao et al, 2018; Farooq et al, 2020; Grunewaldt‐Stöcker et al, 2020; Gao et al, 2021; Zhang et al, 2021a, 2022a), saprophytes (Ma et al, 2012; Wanasinghe et al, 2018), and pathogens (Ghosh & Shamsi, 2014; Ali et al, 2017; Crous et al, 2022). To date, >4500 fungal records on Rosa spp.…”
Section: Discussionmentioning
confidence: 99%
“…The culturable endophytic fungi from R. hybrida were mainly Sordariomycetes and Dothideomycetes, including Acremonium, Aureobasidium, Alternaria, Chaetomium, Cladosporium, Gliocladium, Nigrospora, Nodulisporium, and Phoma (Salgado-Salazar & Cepero de García, 2005). Heinz et al (2018) revealed at least 24 different fungal genera and 30 possible endophytic species in the leaves of this rose. Our previous research found that Sordariomycetes is the dominant class of endophytic fungi from R. roxburghii, and others belong to Agaricomycetes, Dothideomycetes, Eurotiomycetes, Leotiomycetes, and Pezizomycetes (Zhang et al, 2021a(Zhang et al, , 2021b(Zhang et al, , 2022a.…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, biological control agents can have nontarget phenological consequences; for example, fungal entomopathogens can shift germination timing and decrease germination probability (Heinz et al, 2018). On the other hand, phenology regulation can be an advantageous mode of action.…”
Section: Implications For Agriculture and Global Changementioning
confidence: 99%